Alteration in Taste Perception among Young Children following the Use of Oral Irrigants in Pulpectomy Procedure: A Randomised Controlled Trial - S Praveen Kumar; R Ramesh (Journal of Clinical and Diagnostic Research)
Introduction: The impact of oral irrigants on taste perception during pulpectomy procedures focuses on how these sensory experiences affect patient comfort and cooperation. This study aims to identify child-friendly irrigants with natural taste profiles that minimise discomfort and enhance procedural success. Aim: This study evaluated the effects of different oral irrigants-chlorine dioxide, Saline, Chlorhexidine Gluconate, and Sodium Hypochlorite-on taste perception in children undergoing pulpectomy procedures. Materials and Methods: A randomised controlled trial was conducted at Saveetha Dental College and Hospital from July to December 2024, involving 100 children aged 6-9 years undergoing pulpectomy procedures. Participants were randomly assigned to four groups based on the irrigant used: chlorine dioxide, saline, chlorhexidine gluconate, and sodium hypochlorite. The study assessed taste perception using a 5-point Likert scale and a validated questionnaire at baseline and during the second visit. Demographic parameters such as age, gender, and oral health metrics were recorded to ensure group homogeneity. Statistical analysis included paired t-tests, one-way Analysis of Variance (ANOVA), and effect size estimation, with a p-value of <0.05 considered significant. Results: Significant differences in taste alteration scores were observed across the four oral irrigants. Chlorine dioxide exhibited the most substantial reduction in taste alteration scores from T0 (2.96±1.24) to T1 (1.40±0.76), followed by Saline (T0: 3.12±1.01; T1: 2.24±1.27). In contrast, chlorhexidine and sodium hypochlorite showed minimal changes between baseline and follow-up scores. ANOVA revealed statistically significant differences in taste perceptions for chlorine dioxide (p<0.001), Saline (p=0.007), and Chlorhexidine (p=0.033), while Sodium Hypochlorite exhibited borderline significance (p=0.057). Effect size analysis indicated that chlorine dioxide (Eta²=0.398) had the largest impact, particularly influencing sweetness and bitterness perceptions, which played a crucial role in the overall treatment experience. Conclusion: The study underscores the importance of selecting irrigants that balance clinical efficacy with sensory acceptability. Chlorine dioxide demonstrated the greatest impact on taste alteration, necessitating the development of paediatric-friendly formulations to enhance patient cooperation and comfort.